2003
DOI: 10.1038/nn1157
|View full text |Cite
|
Sign up to set email alerts
|

Non-proliferative effects of lysophosphatidic acid enhance cortical growth and folding

Abstract: Lysophosphatidic acid (LPA) is a phospholipid that has extracellular signaling properties mediated by G protein-coupled receptors. Two LPA receptors, LPA(1) and LPA(2), are expressed in the embryonic cerebral cortex, suggesting roles for LPA signaling in cortical formation. Here we report that intact cerebral cortices exposed to extracellular LPA ex vivo rapidly increased in width and produced folds resembling gyri, which are not normally present in mouse brains and are absent in LPA(1) LPA(2) double-null mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
211
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(221 citation statements)
references
References 48 publications
9
211
0
1
Order By: Relevance
“…In iPSC-derived NS/PCs, LPA also signifi cantly decreased proliferation, while a similar trend was observed in hESC-derived NS/PCs but without reaching statistical signifi cance. Hence, our data shows generally consistent results across different iPSC and hESC lines, with some minor interline differences in responsiveness to tiation of human iPSCs, which is in agreement with our previous study using hESCs ( 39 ) and with data obtained in rodents ( 58 ); although other studies found opposite effects in various NS/PCs and neuroblasts ( 14,17,18,38,59,60 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In iPSC-derived NS/PCs, LPA also signifi cantly decreased proliferation, while a similar trend was observed in hESC-derived NS/PCs but without reaching statistical signifi cance. Hence, our data shows generally consistent results across different iPSC and hESC lines, with some minor interline differences in responsiveness to tiation of human iPSCs, which is in agreement with our previous study using hESCs ( 39 ) and with data obtained in rodents ( 58 ); although other studies found opposite effects in various NS/PCs and neuroblasts ( 14,17,18,38,59,60 ).…”
Section: Discussionsupporting
confidence: 93%
“…We found that LPA promoted apoptosis of early human NS/PCs, as revealed by neurosphere formation assay, which is consistent with some NS/PC and neuroblast studies performed in rodents ( 16,17,38,57,58 ) but differs with others in which LPA improves cell survival ( 16,38 ) or proliferation ( 13,35,59 ). In human cells, we previously showed that LPA does not modify apoptosis of older hESCderived NS/PCs ( 39 ) as, when two-week-old hESC-derived within minutes; Fig.…”
Section: Lpa Induces Rhoa Activationsupporting
confidence: 90%
See 2 more Smart Citations
“…Mice deficient in each of the LPA or S1P receptor genes (excluding Lpa 4 , Lpa 5 , and S1p 4 ) have been reported, and double-or triple-knockout mice have been produced for Lpa 1-3 and S1p 1-3 (Contos et al, 2000Kingsbury et al, 2003;Ye et al, 2005Ye et al, , 2008Liu et al, 2000;MacLennan et al, 2001MacLennan et al, , 2006Kono et al, 2004Kono et al, , 2007Cinamon et al, 2004;Jaillard et al, 2005;Herr et al, 2007;Means et al, 2007). However, none of the genetically modified mice reported so far appear to exhibit apparent deficiencies in the formation of somites, possibly because of functional compensation or redundancy among LPA/S1P receptor genes.…”
Section: Combinatorial Regulation Of Lysophospholipids Signaling By Mmentioning
confidence: 99%